Tumour detection and outcomes of surveillance screening in SDHB and SDHD pathogenic variant carriers - Gemma White; Anand Velusamy; Samantha Anandappa; Michael Masucci; Louise A Breen; Mamta Joshi; Barbara McGowan; Johnathan G H Hubbard; Rupert Obholzer; Dimitra Christodoulou; Audrey Jacques; Philip Touska; et al. (Endocrine Connections, 2022)
Objective: Succinate dehydrogenase subunit (SDHx) pathogenic variants predispose to phaeochromocytoma and paraganglioma (PPGL). Lifelong surveillance is recommended for all patients to enable prompt detection and treatment. There is currently limited evidence for optimal surveillance strategies in hereditary PPGL. We aim to detail the clinical presentation of PPGL in our cohort of non-index SDHB and SDHD pathogenic variant carriers. Methods: Retrospective analysis of medical and genetic records from a single tertiary referral centre identified SDHB or SDHD pathogenic variants in 74 non-index cases (56 SDHB and 18 SDHD). Surveillance screening for asymptomatic relatives consisted of annual plasma metanephrine measurement and whole-body MRI with contrast at 3–5 yearly intervals. Results: Twenty-three out of 74 non-index patients (10 SDHB and 13 SDHD) were diagnosed with PPGL, 17 patients through surveillance screening (24 tumours in total) and 6 diagnosed prior to commencement of cascade screening with symptomatic presentation. MRI with contrast identified PPGL in 22/24 screen- detected tumours and 5/24 tumours had elevated plasma metanephrine levels. Penetranc e in non-index family members was 15.2 and 47.2% for SDHB carriers and 71.6 and 78.7% for SDHD carriers at age of 50 and 70 years, respectively. Conclusion: Surveillance screening with combined biochemical testing and imaging enables early detection of PPGL in asymptomatic relatives with SDHx pathogenic variants. The presence of disease at first screen was significant in our cohort and hence further multi-centre long-term data are needed to inform counselling of family members undergoing lifelong surveillance.